Gambaran pengetahuan dan sikap pegawai Politeknik Negeri Manado mengenai kekerasan dalam rumah tangga - Wenas, Asterlita; Sapulete, Margareth; Palandeng, Henry M. F. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Objective: To describe the the knowledge and attitudes of the employees of Manado Polytechnic State employees regarding domestic violence. Methods: The data collection was used with focus group discussions and in-depth interviews with a sample of 11 employees using purposive sampling. Results: The majority of informants knowledge about domestic violence in terms of understanding, factors, and the impact was appropriate but the theory of knowledge in the form of domestic violence is still lacking. The attitude of the informant has had the awareness to do outreach to the community as a form of dedication of employees in the prevention of domestic violence. Summary: Knowledge and attitude that was expected to provide an understanding of domestic violence to the people surrounding and including the socialization of the Act of the Republic of Indonesia on the Elimination of Domestic Violence in order to have a valid understanding about domestic violence. Keywords: knowledge, attitude, domestic violence